Radioactivity Levels Determination and Radiological Hazards in the Drink and Well Water Samples in Baghdad - Naji Jameel, Athraa (Al-Nahrain Journal of Science, 2024)
Samples have been collected from two sources of water: drinking water and well water, for various depths for the Al- Bayaa region in Baghdad using a gamma spectrometer with the Germanium HPGe detector. The results of the analysis show that the average activity concentrations were 1.19±0.5 for 238U, 0.96±0.2  for 232Th, and 10.5±0.5 Bq/L for 40 K in drinking water samples and 1.77±0.5 for 238 U, 1.03±0.2 for 232 Th, and 12.6± 0.5 Bq/L for 40 K in well water samples, respectively. The results were less than their recommended. The study also calculated the radiation hazards represented by the radium equivalent activity, Gamma index, Hazard Index, Absorbed gamma dose rate, Annual effective dose equivalent, and Lifetime cancer risk. All the radiological parameters in water drinking and well samples were within the range of the global limit; thus the water drinking and well water was Safe and free from radioactive contamination in that area.